Determining Safe Limits for Significant Task Parameters during Manual Lifting. (April 2014) - Singh, Ravindra Pratrap; Batish, Ajay; Singh, Tejinder Pal
This experimental study investigated the effect of lifting task parameters (i.e., lifting weight, frequency, coupling, asymmetric angle, and vertical, horizontal, and travel distances) for various dynamic human lifting activities on the ground reaction forces of workers. Ten male workers loaded containers from different levels asymmetrically during experimental trials. The experimental design evolved using Taguchi's Fractional Factorial Experiments. Three factors (lifting weight, frequency, and vertical distance) were observed to be significant. The results showed that vertical reaction forces increase when workers lift weight from floor to shoulder height frequently. It was also observed that instantaneous loading rate increases with more weight, vertical distance, and frequency; a significant extra loading rate is required to change the lower level of load, frequency, and vertical distance to higher levels. Safe limits for significant factors were determined to result in optimal performance of the manual lifting task.